Transdifferenz und Transkulturalität Migration und Alterität in den Literaturen und Kulturen Österreich-Ungarns - Millner, Alexandra (Lettre, 2018)
What are the possibilities for shaping the modern individual offered by transdifferent moments? This book sheds light on the overcoming of social borders in the cultural context of the late Habsburg Monarchy.